2017
DOI: 10.1016/j.engfailanal.2017.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion failure analysis of hearing aid battery-spring contacts

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…and are manufactured using materials with good electrical and soldering properties such as Ag, Cu, Al, Sn, Ni, and Au. Several studies in the past have shown the corrosion failures of electrical components in the presence of harsh environmental conditions and ionic contaminants (Waterhouse and Taylor, 1974;Comizzoli et al, 1986;Ohring, 1998;Gudla and Ambat, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and are manufactured using materials with good electrical and soldering properties such as Ag, Cu, Al, Sn, Ni, and Au. Several studies in the past have shown the corrosion failures of electrical components in the presence of harsh environmental conditions and ionic contaminants (Waterhouse and Taylor, 1974;Comizzoli et al, 1986;Ohring, 1998;Gudla and Ambat, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing aids are low-power electronic devices that are being used worldwide in a variety of locations that can impose different climatic conditions during its operation e.g., tropical, arid, dry, etc. Consequently, HAs are prone to corrosion failures due to moisture layer formation on its electronic parts like print circuit board assembly (PCBA), electrical contacts, etc., under humid conditions as well as upon exposure to bodily fluids such as human sweat and body oils (Gudla and Ambat, 2017). In addition, the failure of ZAB cells in the form of KOH leakage can easily occur with accelerated rates due to the prevalent corrosive environments in which HA devices are operated.…”
Section: Introductionmentioning
confidence: 99%
“…Those previous studies focused mainly on failure analysis at the component level without holistically considering the whole device synergistically with the place of use. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Those previous studies focused mainly on failure analysis at the component level without holistically considering the whole device synergistically with the place of use. [20,21] The present investigation focused on the root cause failure analysis based on the physics of failure (PoF) approach to identify various failure modes and mechanisms for the field-failed HA devices. Failed HA devices from three different markets, such as Europe, United States, and Japan, that represent to some extent the tropical, subtropical, and coastal areas, were analyzed for corrosion failures.…”
mentioning
confidence: 99%
“…While many precautionary measures have been adopted to prevent the corrosion of solder joints under normal operating conditions, the complete protection from the ever-present corrosive ions has yet to be achieved (Liu et al , 2015a, 2015d). For example, it was reported that circuit for hearing-aid device was prone to human perspiration and environmental pollutant (Gudla and Ambat, 2017). Device failure caused by trace amounts of ionic contaminants are potentially more severe now than previously thought, given the increase in the number of electronic components tightly packed onto electronic circuits.…”
Section: Introductionmentioning
confidence: 99%